Community Pursuing the Dream, Living the Reality - Keller, Suzanne (Princeton University Press, 2018)
This book tells the story of how a human community comes to be and how aspirations for the good life confront the dilemmas and detours of real life. Suzanne Keller combines penetrating analysis of classic ideas about community with a remarkable and unprecedented thirty-year case study of one of the first "planned unit developments" in America and the first in New Jersey. Twin Rivers, this pioneering venture, featured townhouses and shared spaces for children's play and adult work and play in a society that stresses individual over collective goals and private over public concerns.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Nov 2018)
Keywords: Geschichte 1970-2000; Communities; Community life -- Case studies; Community life -- New Jersey -- Case studies; Gesellschaftsleben; Gemeindeentwicklung; Stadtsoziologie; Gemeinde; New Jersey; USA; Twin Rivers, NJ; Fallstudiensammlung